2021
DOI: 10.1002/adem.202001191
|View full text |Cite
|
Sign up to set email alerts
|

MAX Phases as Nanolaminate Materials: Chemical Composition, Microstructure, Synthesis, Properties, and Applications

Abstract: Ceramics is one of the oldest materials prepared and used by human beings. Ancient ancestors started to make pottery by forming and burning clay since the earliest civilizations. Ancient people started to fabricate burnt claywares since %6500 B.C., and clayware as a commercial product was available by %4000 B.C. [1] In modern society, as one of the largest branches in material family, ceramics have been developed and used in almost every fields of human beings' lives. In some senses, ceramics and metals posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 171 publications
(405 reference statements)
0
45
0
Order By: Relevance
“…MAX phases are a class of layered transition metal carbides, nitrides, and carbonitrides in a chemical formula of M n+1 AX n (M is an early transition metal element, A represents an element mainly from groups 13–16, X is C and/or N, n = 1–4). [ 1–4 ] Typically, MAX phases possess a unique hexagonal crystalline structure with a space group of P 6 3 / mmc , in which strong covalent bonded M n+1 X n atomic layers are interleaved by A layers via weak metallic bonds, enabling MAX phases with good oxidation resistance, high electrical and thermal conductivities, holding great potential in the fields of mechanics, electrics, and protective coatings. [ 2,5–8 ] In a recent decade, MAX phases have been widely utilized to synthesize their derivative 2D MXenes (M n+1 X n T x , T is the surface functional group) by selective extraction of A layers.…”
Section: Introductionmentioning
confidence: 99%
“…MAX phases are a class of layered transition metal carbides, nitrides, and carbonitrides in a chemical formula of M n+1 AX n (M is an early transition metal element, A represents an element mainly from groups 13–16, X is C and/or N, n = 1–4). [ 1–4 ] Typically, MAX phases possess a unique hexagonal crystalline structure with a space group of P 6 3 / mmc , in which strong covalent bonded M n+1 X n atomic layers are interleaved by A layers via weak metallic bonds, enabling MAX phases with good oxidation resistance, high electrical and thermal conductivities, holding great potential in the fields of mechanics, electrics, and protective coatings. [ 2,5–8 ] In a recent decade, MAX phases have been widely utilized to synthesize their derivative 2D MXenes (M n+1 X n T x , T is the surface functional group) by selective extraction of A layers.…”
Section: Introductionmentioning
confidence: 99%
“…[118] A high surface area is an important characteristic for various fields such as catalysis. [130] In another study, layered structures of Ti 3 C 2 T x MXene were prepared and modified with amino groups and then further treated with a borate affinity sorbent, 4-formylphenylboronic acid (4-FPBA), to produce Fe 3 O 4 @Ti 3 C 2 -BA. BET analysis revealed that this nanocomposite possessed a high specific surface area of 33.77 m 2 g −1 (Table 1).…”
Section: Betmentioning
confidence: 99%
“…A special family of transition metal carbides is constituted by multilayer metal carbides with a 2D nanosheet structure similar to that of graphene, belonging to the group of compounds called MXenes. The term MXenes denotes carbides and nitrides of transition metals, with the general formula M n+1 X n T x , where n = 1, 2, 3, or 4, M refers to the transition metal (M = Sc, Ti, V, Cr, Mn, Y, Zr, Nb, Mo, Hf, Ta, and W [23,161]), and X refers to the p-block element (silicon, aluminum, gallium), while T describes the type of terminal groups (-O, -OH, -F, -Cl) in the amount of x per selected unit. They are obtained by selectively removing component A from the ternary MAX matrix.…”
Section: Max Matrices and Mxenesmentioning
confidence: 99%